The Most Cited Articles from the Top-5 Journals (1991-2015) - Laurent Linnemer; Michael Visser (Center for Economic Studies and ifo Institute (CESifo), 2016)
This report documents what are the most cited articles published in the top-5 economics journals during the period 1991-2015. EconLit is used to collect bibliographic information about these articles, and we gathered yearly citations for each paper through the Web of Science database. We present different sorts of citation lists. Our most basic one ranks articles on the basis of the cumulated number of citations received between year of publication and 2015. To facilitate the comparison of articles of different ages, we also consider rankings by subperiods, and on the basis of normalized citations per year. Finally we report lists by field of economic research, as defined by the JEL codes of the papers. The report contains Internet links to all articles, allowing an easy and direct access to arguably the most influential economics literature published in the last 25 years.
Keywords: A14; 330